Downregulating VAC14 in Guard Cells Causes Drought Hypersensitivity by Inhibiting Stomatal Closure - Wang, Zong-Qi; Liu, Qi; Wu, Ju-Hua; Li, Juan; He, Jun-Min; Zhang, Yan; Li, Sha (Frontiers in Plant Science, 2020)
Stomata are a key land plant innovation that permit the regulation of gaseous exchanges between the plant interior and the surrounding environment. By opening or closing, stomata regulate transpiration of water though the plant; and these actions are coordinated with acquisition of CO2 for photosynthesis. Stomatal movement is controlled by various environmental and physiological factors and associates with multiple intracellular activities, among which the dynamic remodeling of vacuoles plays a crucial role. Phosphatidylinositol 3,5-bisphosphate [PI(3,5)P2] is critical for dynamic remodeling of vacuoles. Its production requires a PI(3,5)P2-metabolizing complex consisting of FAB1/PIKfyve kinases, SAC phosphatases, and the scaffolding protein VAC14. Although genetic or pharmacological downregulation of PI(3,5)P2 causes hyposensitivity to ABA-induced stomatal closure, whether the effect of PI(3,5)P2 on stomatal movement is cell-autonomous and the physiological consequences of its reduction were unclear. We report that downregulating Arabidopsis VAC14 specifically in guard cells by artificial microRNAs (amiR-VAC14) results in enlarged guard cells and hyposensitivity to ABA- and dark-induced stomatal closure. Vacuolar fission during stomatal closure is compromised by downregulating VAC14 in guard cells. Exogenous application of PI(3,5)P2 rescued the amiR-VAC14 phenotype whereas PI(3,5)P2 inhibitor YM201636 caused wild-type plants to have inhibited stomatal closure. We further show that downregulating VAC14 specifically in guard cells impairs drought tolerance, suggestive of a key role of guard cell-produced PI(3,5)P2 in plant fitness.